PRELIMINARY INVESTIGATION OF ANTIGEING PROPERTIES OF TWO KINDS OF MALLEINS - S. AL-KASHALY , SALAH, (The Iraqi Journal of Veterinary Medicine, 1996)
The antigeic composition of two kinds of malleins (Old mallein and PPD mallein) were analysed by gel filtration chromatography on sephacryl S 300 column. Two major protein peaks were determined and were termed peak 1 (mol. wt> 10-6 daltons) and peak 2 (mol. wt < 5000 daltons). Fractions of mallein were tested for its haemagglutination inhibition activity (HI) and delayed type hypersensitivity reaction (DTH) in a P. mallei sensitized guinea pigs. Most of the HI activity of the fractions was correlated to the fractions of peak 1. Moreover peak 1 produced good DTH reaction in sensitied guinea pigs, but peak 2 failed to produce satisfactory results. It was concluded that the antigenic activity of both Old and PPD malleins were associated with the high molecular weight protein fraction which is found in both mallein preparations.